THE EFFECT OF VARIETY PECULIARITIES ON WINTER WHEAT GRAIN QUALITY - Zhemela, H. P.; Barabolia, O. V.; Tatarko, Y. V.; Antonovskiy, O. V. (Scientific Progress & Innovations, 2020)
The topicality of cultivating high-quality winter wheat as a main food crop in Ukraine and valuable in crop rotation system has been substantiated in the article. The estimation of physical and chemical properties of winter wheat varieties was given in the article with the aim to find better characteristics for further using grain. Winter wheat grains of the following cultivars were used: Orzhytsia, Poltavchanka, Tsarychanka, Zelenyi Hai, Karmeliuk, Ariivka, Liutenka, Sahaidak, and Dykanka (selected in Poltava State Agrarian Academy). Laboratory testing of winter wheat grain quality was conducted at the laboratory of Poltava State Agrarian Academy certified by the State Consumer Standard of Ukraine. Physical and chemical grain quality indices of winter wheat were determined in accordance with generally accepted methods, which correspond to the State Standard or State Standard of Ukraine. The study showed high germination energy of all winter wheat cultivars; Zelenyi Hai (96 %) and Tsarychanka (94 %) cultivars had the highest germination capacity indices. Orzhytsia cultivar had the lowest index (86 %), which also indicated good germinating power. As to the effect of variety properties on thousand-kernel weight, Zelenyi Hai cultivar had the highest index(48.0 g) and Orzhytsia had the lowest one (39.7 g). The highest grain hardness in tested samples was registered in Zelenyi Hai cultivar (97 %) and the lowest – in Poltavchanka (70 %). Thus, it can be concluded, that these cultivars are suitable for bakery products. The analysis of variety property effect on chemical composition of winter wheat grain was conducted by the following indices: gluten content, number of falling, protein content, and sedimentation value. It was registered that Liutenka cultivar had the largest gluten content (37 %) and Orzhytsia (30 %), Dykanka (31 %) and Zelenyi Hai (31 %) – the smallest ones. Determining gluten deformation showed that the second group prevailed and indices varied from 88 to 102 units. The results of studying the number of falling showed that winter wheat grain had the indices from 206 (which was acceptable) to 452 (the increased index, so the quality of bakery products may not be the best). The studying of protein content testified that all the nine winter wheat varieties corresponded to the recognized standards. Orzhytsia variety had the lowest protein content (13.6 %), while Lituenka had the highest one (16.9 %). The estimation of sedimentation value showed that the majority of the presented samples had high indices – over 50 ml and more. Only one grain sample of Ariivka winter wheat variety had the average index of 34 ml. Thus, two varieties, Zelenyi Hai and Liutenka, which showed the best results as to all the parameters and indices, were chosen, Positive dynamics has been registered in indices of almost all varieties, which is the proof of their capacity to give stable coming-up and resistance to unfavorable conditions.